Improving The System Of Methodological Training Of Future Pedagogical Masters For Creativism Activities - Choriev Ikrom Abdushukurovich (Genius Journals, 2023)
The article describes creative activities as a unique complex process that reflects the task of forming the competence of prospective forecasting of the strategy of continuous education and modernization of education. The author suggests that traditional ways, some approaches are person-oriented, technological and creative approaches as a solution to the problem.The article deals with the pedagogical regularities of methodological and methodical approaches, that is, the factors of effective formation of a master pedagogue in the modernization of the educational process, were fundamentally justified.
Keywords: Improvement; system; methodological; training